Deficiency of skeletal membrane protein band 4.1 in homozygous hereditary elliptocytosis. Implications for erythrocyte membrane stability. - Tchernia, G (1981)
Erythrocytes from three patients with severe hemolytic anemia, marked erythrocyte fragmentation, and elliptocytic poikilocytosis, were studied in terms of both their membrane protein composition and their mechanical characteristics. Erythrocytes from the patients' parents and one minimally affected and one normal sibling were also studied. Morphologic observations implied that the severely affected patients suffered from homozygous hereditary elliptocytosis because erythrocytes of both parents and the one minimally affected sibling showed moderate elliptocytosis on smear, whereas those of an unaffected sibling had normal morphology. The parallel findings of markedly reduced levels of band 4.1 in the erythrocyte membrane proteins of the patients and an intermediate reduction in the cells of the parents and the putative heterozygous sibling, suggest that the elliptocytic shape of the cells was related to the reduced levels of band 4.1. Additional studies showed marked abnormalities in cellular deformability and membrane fragility in the erythrocytes from the homozygous patients. Importantly, these changes were also closely proportional to the reduced levels of band 4.1, suggesting a central role for this protein in the maintenance of normal membrane stability and normal cell shape. It seems likely that this role for band 4.1 is intimately related to its known biochemical connection to the "membrane skeleton" through its linkage with spectrin and actin.